(untitled) (Jurnal Ilmu Pendidikan dan Sains: Visioedusains, 2025)
This study aims to determine the influence of Outdoor Learning learning methods on improving environmental literacy and environmental care attitudes in science lessons in class VII MTs Hamzanwadi NW Gelogor Kediri, West Lombok. This type of research is quasi-experimental. The sampling technique used purposive sampling with the subjects of grade VII students consisting of class VII A as the control class (33 students) and class VII B as the experimental class (33 students). The research instruments include environmental literacy tests and environmental care attitude questionnaires. The data obtained was analyzed using SPSS 20 with a paired sample t-test and an N-Gain test. The results of the paired sample t-test showed a significance value (2-tailed) of 0.000 < 0.05, which means that there is a significant influence of the Outdoor Learning method on improving environmental literacy and students' environmental care attitudes. Meanwhile, the results of the N-Gain test showed an average score of 76.6% for environmental literacy and 67% for environmental care attitudes, which are included in the category of quite effective. These findings suggest that Outdoor Learning can be an effective learning strategy in fostering students' awareness and concern for the environment through hands-on learning experiences.